Characterizing the laser drilling process of oil shale using laser-induced voltage. (November 2020) - Zhang, Shanzhe; Huang, Jianfeng; Miao, Xinyang; Zhan, Honglei; Liang, Huaqing; Zhao, Kun
Highlights: Laser-induced voltage (LIV) was applied to characterize the laser drilling (LD) process of oil shale. An exponential model was applied to explain the carrier transportation process. The perforation rate was employed to characterize surface spallation and rock puncture. Abstract: In this study, the oil shale surface was irradiated using an ultraviolet (UV) laser. Since the UV photon energy exceeded the band-gap of the oil shale, the photoexcited carriers were generated and the inter-band transition was induced. Thus the laser-induced voltage (LIV) occurred under an application of bias voltage. The peak value of LIV signal strongly depended on the drilling time. The voltage waveforms were fitted well by the double-exponential function. The whole drilling process was divided into two distinct stages corresponding to surface spallation and rock puncture, respectively. The results indicated that LIV can be employed to characterize the laser drilling process of oil shale.